Differences in technique between sprinters and distance runners at equal and maximal speeds - Bushnell, T.; Hunter, I. (Sports Biomechanics, 2007)
In the finishing kick of a distance race, maximizing speed becomes the focus even if economy may be sacrificed. If distance runners knew how to alter their technique to become more sprint-like, this process could be more successful. In this study, we compared the differences in technique between sprinters and distance runners while running at equal and maximal speeds. Athletes consisted of 10 Division I distance runners, 10 Division I sprinters, and 10 healthy non-runners. They performed two tests, each consisting of a 60-m run on the track: Test 1 at a set pace of 5.81 m/s, while Test 2 was maximal speed. Video was collected at 180 Hz. Significant differences (P < 0.05) between the sprint and distance groups at maximal speeds were found in the following areas: speed, minimum hip angle, knee extension at toe-off, stride length, contact time, and recovery knee at touchdown. In Test 1, sprinters and distance runners displayed many of the same significant differences. The control group was similar to the distance group in both trials. As distance runners attempt to sprint, the desired adjustments do not necessarily occur. Distance runners may benefit from biomechanical interventions to improve running speed near the end of a race.